Preparation and Properties of Graft-Modified Bagasse Cellulose/Polylactic Acid Composites. Issue 1 (31st December 2023) - Wang, Yanan; Xu, Hao; Huang, Lijie; Han, Xiaoxue; Wei, Zhehao; Mo, Qi; Wang, Xiyue; Li, Yishan
ABSTRACT: Fiber reinforcement is the most common method for modifying polylactic acid (PLA). However, poor compatibility between fibers and PLA, especially at high cellulose contents, can promote cellulose agglomeration in the continuous phase, which damages the mechanical properties of composite materials. To address these issues, bagasse cellulose (BC) was used as a substrate and bifunctional glycidyl methacrylate (GMA) was used as a reactive monomer for graft modification. GMA-modified BC (BC-GMA)/PLA composite materials with different particle sizes were prepared using a blending grafting method, and the influence of the type and content of BC-GMA on the mechanical properties of the composite materials was explored. During the grafting modification of BC, a longer reaction time was found to result in smaller BC particles and a higher degree of grafting. For BC-GMA, the degree of grafting reached 27.02% with a maximum thermal decomposition temperature of 359.31°C. Furthermore, the BC-GMA/PLA composite material had a greater relative crystallinity of PLA, indicating that BC-GMA was evenly dispersed in the continuous phase. This study demonstrates that grafting modification can successfully achieve high cellulose loading in composite materials and thus reduce the production costs of PLA-based packaging materials. GRAPHICAL ABSTRACT: